Correlation of clinical sepsis definitions with microbiological characteristics in patients admitted through a sepsis alert system; a prospective cohort study - David Yu; David Unger; Christian Unge; Åsa Parke; Jonas Sundén-Cullberg; Kristoffer Strålin; Volkan Özenci (BMC, 2022)
Abstract Background Sepsis was recently redefined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. With this redefinition (Sepsis-3), clinical and microbiological characteristics of patients with sepsis may differ from the patients fulfilling the previous definition (Sepsis-2). Purpose To describe differences in clinical and microbiological characteristics of sepsis episodes between Sepsis-3 and Sepsis-2. The secondary aim was to compare blood culture outcomes between episodes fulfilling Sepsis-3 and Sepsis-2 criteria, respectively. Methods A prospective study design was used to include patients presenting with clinically suspected sepsis in the emergency department. Six blood culture bottles were collected from each patient. Blood cultures were described as having clinically relevant growth, contaminant growth, or no growth. Clinical and laboratory data were collected from medical records and the laboratory information system. Results The analysis included 514 episodes. There were 357/514 (79.5%) Sepsis-3 and 411/514 (80.0%) Sepsis-2 episodes. In total, 341/514 (66.3%) episodes fulfilled both Sepsis-3 and Sepsis-2 criteria. Blood cultures were positive for clinically relevant growth in 130/357 (36.1%) and 145/411 (35.3%) episodes in Sepsis-3 and Sepsis-2, respectively. Other clinical and microbiological characteristics did not differ between Sepsis-3 and Sepsis-2. Conclusions A high proportion of patients included through a sepsis alert system fulfilled both Sepsis-3 and Sepsis-2 criteria. The performance of blood cultures in detection of microorganisms was poor and were similar in Sepsis-3 and Sepsis-2 patients.